Pentingnya Pengelolaan Kelas Dalam Pembelajaran - Ilmiahwati, Tibta; Wijayanto, Sukma (Prosiding University Research Colloquium, 2021)
Class management is needed because the behaviour and actions of students every day and every time will change often. It is possible that today students can study ip peace, but tomorrow is not necessarily . The class is always dynamic with the form of behaviour, actions, attitudes, mental, and emotional children.Professional teachers are teachers who are able to manage the class well. In the classroom, all aspects of teaching and learning meet and process. Teachers with all their abilities, and students with all their backgrounds and individual characteristics, the curriculum with its components, learning materials and resources with the subject matter meet and integrate in the classroom. The result of education and teaching are largely determined by what happens in the classroom. For that, the class should be managed professionally.